Drought-Enhanced Xylem Sap Sulfate Closes Stomata by Affecting ALMT12 and Guard Cell ABA Synthesis. Issue 2 (26th April 2017) - Malcheska, Frosina; Ahmad, Altaf; Batool, Sundas; Müller, Heike M.; Ludwig-Müller, Jutta; Kreuzwieser, Jürgen; Randewig, Dörte; Hänsch, Robert; Mendel, Ralf R.; Hell, Rüdiger; Wirtz, Markus; Geiger, Dietmar; et al.
Abstract : Reduced unloading and enhanced loading of sulfate increased xylem sap sulfate during early drought, which affects the opening of the ALMT12 channel and induces guard cell expression of the key step in ABA synthesis, NCED3. Abstract: Water limitation of plants causes stomatal closure to prevent water loss by transpiration. For this purpose, progressing soil water deficit is communicated from roots to shoots. Abscisic acid (ABA) is the key signal in stress-induced stomatal closure, but ABA as an early xylem-delivered signal is still a matter of debate. In this study, poplar plants ( Populus × canescens ) were exposed to water stress to investigate xylem sap sulfate and ABA, stomatal conductance, and sulfate transporter ( SULTR ) expression. In addition, stomatal behavior and expression of ABA receptors, drought-responsive genes, transcription factors, and NCED3 were studied after feeding sulfate and ABA to detached poplar leaves and epidermal peels of Arabidopsis ( Arabidopsis thaliana ). The results show that increased xylem sap sulfate is achieved upon drought by reduced xylem unloading by PtaSULTR3;3a and PtaSULTR1;1, and by enhanced loading from parenchyma cells into the xylem via PtaALMT3b. Sulfate application caused stomatal closure in excised leaves and peeled epidermis. In the loss of sulfate-channel function mutant, At almt12, sulfate-triggered stomatal closure was impaired. The QUAC1/ALMT12 anion channel heterologous expressed in oocytes was gated open by extracellular sulfate. Sulfate up-regulated the expression of NCED3, a key step of ABA synthesis, in guard cells. In conclusion, xylem-derived sulfate seems to be a chemical signal of drought that induces stomatal closure via QUAC1/ALMT12 and/or guard cell ABA synthesis.